2021
DOI: 10.2196/23029
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Intervention to Increase Uptake and Adherence of an Internet-Based Program for Depression and Anxiety (Enhancing Engagement With Psychosocial Interventions): Randomized Controlled Trial

Abstract: Background Psychosocial, self-guided, internet-based programs are effective in treating depression and anxiety. However, the community uptake of these programs is poor. Recent approaches to increasing engagement (defined as both uptake and adherence) in internet-based programs include brief engagement facilitation interventions (EFIs). However, these programs require evaluation to assess their efficacy. Objective The aims of this hybrid implementation e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“… 32 , 33 , 36 , 43 , 44 , 47 , 49 The remaining seven studies reported no differences between the strategy and no-strategy groups across all measures of engagement. 26 , 28 , 29 , 35 , 39 , 41 , 46 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 32 , 33 , 36 , 43 , 44 , 47 , 49 The remaining seven studies reported no differences between the strategy and no-strategy groups across all measures of engagement. 26 , 28 , 29 , 35 , 39 , 41 , 46 …”
Section: Resultsmentioning
confidence: 99%
“…All studies offered feedback or suggestions based on users’ past programme use or individual context. These were delivered via in-app push notifications, 30 , 31 , 33 , 43 email, 28 , 29 internet-based platform 26 and text message. 45 Four studies evaluated the effect of tailored feedback on engagement compared to no-strategy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was anticipated that the relative reach (ratio of uptake to exposure) would be highest in the social media pathway, whereas the cost per enrolled participant would consequently be lower in this pathway. In addition, we hypothesized that engagement with the program (based on adherence; module completion) would be lowest among people recruited through social media, as this group had the least possibility of human contact in the recruitment process [ 46 ]; that is, the higher uptake on the web may come at the expense of engagement with the intervention. We did not have any specific hypotheses regarding outcomes for the pharmacy pathway, as this pathway has not been investigated previously in e-mental health implementation research.…”
Section: Introductionmentioning
confidence: 99%